Experimental investigations for applying PESS to disaster relief PTHs. (February 2019) - Wang, Caixia; Deng, Shiming; Liu, Xuefeng; Fang, Guanyu; Chen, Wenjing; Long, Enshen; Niu, Jianlei
Abstract: In disaster relief reconstructions, the severe indoor thermal environment of the prefabricated temporary house (PTH) limits its massive utilization. Here, the application of phase change material energy storage system (PESS) has been proposed in the full-scale experimental PTH. In the experimental investigations, a movable PESS was designed aiming at regulating the indoor environment of the PTH during the daytime in hot summer, by charging the cool energy during the nighttime. The movable PESS revealed positive impacts on the indoor environment regulation in the experimental PTH. In addition, the distance between the PESS and the west wall also had influences on the cool energy discharging of the PESS and the indoor thermal environment of the experimental PTH.